Exploration of Occupational Safety Practices in Chemical Waste Management: A Case Study in the Printing Industry - Juwairiah Juwairiah (Jurnal Inovasi Pendidikan dan Sains, 2025)
The printing industry generates chemical waste that has the potential to endanger workers' health and the environment. This study aims to explore occupational safety practices in chemical waste management within the printing industry and to identify challenges in the implementation of occupational health and safety (OHS) procedures. This research employed a qualitative case study method, with data collected through semi-structured interviews, direct observations, and document analysis. The primary research instrument was the researcher, supported by interview guidelines, observation sheets, and document recording formats. Informants were selected using purposive sampling, consisting of production technicians, OHS (Occupational Health and Safety) department heads, and waste management personnel. The data were analyzed using the Miles & Huberman technique, which includes data reduction, data display, and conclusion drawing. The results indicated that the use of personal protective equipment (PPE) and the implementation of standard operating procedures (SOPs) for chemical waste management were not yet optimal, and occupational safety training remained predominantly theoretical with limited practical application. In conclusion, there is a need for more intensive practical training, updated and easily accessible SOPs, and enhanced worker awareness